Respuesta :

(c+8)(c-8)

3(2y+5)(2y-5)

There are no like terms so it's still ab^2-b

Answer:

a)

[tex]c^2-64=(c-8)(c+8)[/tex]

b)

[tex]12y^2-75=3(2y-5)(2y+5)[/tex]

c)

[tex]ab^2-b=b(ab-1)[/tex]

Step-by-step explanation:

a)

[tex]c^2-64[/tex]

This expression could also be given by:

[tex]c^2-8^2[/tex]

Now, we know that:

[tex]a^2-b^2=(a-b)(a+b)[/tex]

Hence, we have:

[tex]c^2-64=(c-8)(c+8)[/tex]

b)

[tex]12y^2-75[/tex]

[tex]12y^2-75=3(4y^2-25)[/tex]

which is further given by:

[tex]12y^2-75=3((2y)^2-5^2)\\\\12y^2-75=3(2y-5)(2y+5)[/tex]

c)

[tex]ab^2-b[/tex]

we take out common b from both the terms to get:

[tex]ab^2-b=b(ab-1)[/tex]